Vícenásobné nádorové onemocnění plic - kazuistika a přehled literatury - Chovanec, Z; Čapov, I; Peštál, A; Benej, M; Páral, M (Klinicka onkologie, 2016)
BACKGROUND: Multiple primary lung cancer is a relatively rare nosological entity. This case report is a reminder and points out the pitfalls of its diagnosis and therapy. CASE REPORT: A 62-year-old patient was indicated for surgical therapy for non-small cell lung cancer of the middle lobe and right lung, which were diagnosed during a screening investigation after the patient had undergone previous mastectomy of the right breast with axillary dissection for invasive ductal adenocarcinoma. Another infiltration in the lower lobe of the same lung was removed at the same time and was classified as a primary lung carcinoma; it was a synchronous lung cancer. CONCLUSION: Lung cancer presenting with more than one primary lesion in the lung is a rare nosological entity that can be classified into two types; synchronous and metachronous. Whereas synchronous cancers arise in the lung at the same time, metachronous cancers develop after treatment of the initial lesion. The incidence of multiple lung cancer is increasing due to earlier diagnosis and because successful treatment of the initial cancer at an early stage has led to an increase in patient survival, resulting in an increase in the interval between detection of the initial cancer and detection of the second. Smoking is one of the main risk factors. Diagnosis is made difficult because metastatic disease must be excluded. Basic information is obtained from a biopsy of the tumor. The staging of more than one primary lung cancer is complex and needs to be meticulous if curative resection is being contemplated. Magnetic resonance imaging of the brain and fluorodeoxyglucose positron emission tomography should be performed to evaluate for extra-thoracic metastases. KEY WORDS: lung carcinoma - multiple cancer disease - synchronous - metachronous - diagnosis - therapyThe authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study.The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 22. 2. 2016Accepted: 20. 4. 2016.
Keywords: nádory plic; nemalobuněčný karcinom plic; Female; mnohočetné primární nádory; Lung Neoplasms; Humans; ženské pohlaví; Neoplasms, Multiple Primary; lidé; Middle Aged; lidé středního věku; Positron Emission Tomography Computed Tomography; PET/CT; Carcinoma, Non-Small-Cell Lung